Harry goes to dog school - Menchin, Scott (New York : HarperCollins publishers., 2012)
Preferring to be a dog instead of a boy despite his parents' efforts to convince him otherwise, Harry barks, bites, and rolls around until he is sent to an academy for dogs, where he struggles to follow the school's dog-training methods.